The Smash Ability in Volleyball Games: The experimental study of teaching style and motor ability - Halim, Abdul; Tangkudung, James; Dlis, Firmansyah (Journal of Education, Health and Sport, 2019)
Smash Ability in low volleyball games can affect to the student achievement. This study as a whole aims to determine the impact of differences and interactions from teaching styles and motor skills on the achievement of smash ability in volleyball games. This research method uses an experiment of treatment by level 2x2 design. This research was conducted in National High School of 4 Sinjai Timur, the study sample was 54 students in grade 8. The results of this study indicate that: (1) there is a significant difference in influence between self-check teaching styles and reciprocal to the outcomes of volleyball smash ability learning, (2) there is a significant interaction influence between teaching styles and motor ability to the outcomes of volleyball smash ability learning, (3) there is a significant differences of the smash ability in volleyball games using a self-check teaching styles and reciprocal in groups of students with high motor skills, and (4) there is a significant differences of the smash ability in volleyball games using a self-check teaching styles and reciprocal in groups of students with low motor ability.